2018
DOI: 10.1159/000484314
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Placental Perfusion in the Preeclampsia L-NAME Rat Model with High-Field Dynamic Contrast-Enhanced MRI

Abstract: Purpose: To evaluate placental function and perfusion in a rat model of preeclampsia infused with L-nitro-arginine methyl ester (L-NAME) by dynamic contrast-enhanced (DCE) MRI using gadolinium chelates. Methods: Pregnant female Sprague-Dawley rats were fitted on embryonic day 16 (E16) with subcutaneous osmotic minipumps loaded to deliver, continuously, L-NAME (50 mg/day per rat; case group) or saline solution (control group). DCE MRI was performed on E19 using gadolinium chelates and a 4.7-T MRI apparatus for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In this study, we constructed preeclampsia rat models through L-nitroarginine methyl ester [ 17 ], finding that blood pressure and 24 h proteinuria levels of the rats significantly increased and the number of fetal rats and weight of them and the weight of placenta in them decreased significantly. In addition, we also found that the apoptosis rate of placenta tissue cells of the rats increased significantly, while after intervention of low molecular heparin, those manifestations were improved.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we constructed preeclampsia rat models through L-nitroarginine methyl ester [ 17 ], finding that blood pressure and 24 h proteinuria levels of the rats significantly increased and the number of fetal rats and weight of them and the weight of placenta in them decreased significantly. In addition, we also found that the apoptosis rate of placenta tissue cells of the rats increased significantly, while after intervention of low molecular heparin, those manifestations were improved.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic signal intensity curves demonstrate the relative signal intensity in a region of interest plotted over time. MR images were analyzed on a workstation using software (PhysioD3D) [ 19 ] that was locally developed using MATLAB (R2012b; MathWorks, USA) [ 9 14 ]. Manual segmentation of the arterial input function (AIF) and the placenta was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Functional MRI has already been used to evaluate cerebral, cardiac, tumor and hepatic perfusion [ 6 8 ], and could provide new insights into placental function. Our team has previously developed animal models of dynamic contrast enhanced (DCE) MRI [ 9 14 ]. The feasibility of DCE MRI has also been demonstrated in primates [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…gadolinium chelate) has been used to quantify placental function such as blood volume, blood flow, oxygenation and perfusion rate in different placental compartments. 169 Recently, DCE-MRI has been used to investigate placental perfusion in hypoxic-induced FGR rodents, [170][171][172] pre-eclamptic rats (induced by continuous delivery of L-nitro-arginine methyl ester to chronically inhibit nitric oxide synthase) 173 and prenatal alcohol exposure in monkeys. 151 Placental blood flow and perfusion rate were reduced significantly in the animal models of hypoxia and ethanol exposure 151,170,171 but not in a model of pre-eclampsia.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…151 Placental blood flow and perfusion rate were reduced significantly in the animal models of hypoxia and ethanol exposure 151,170,171 but not in a model of pre-eclampsia. 173 A combination of DCE-MRI and fluorescence imaging has also been used to delineate and quantify the volume of maternal and fetal compartments in mouse placenta. 174 Therefore, both BOLD-MRI and DCE-MRI can be used for in vivo 3D assessment of placental and fetal function, blood flow and oxygenation.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%